FRAMING THE ROHINGYA CRISIS: A COMPARATIVE ANALYSIS OF NEWS MEDIA DISCOURSE IN INDONESIA AND MALAYSIA - Muhammad Hafizh Fariadhi; Jaufillaili; Turini Erawati; Setia Budiyanti (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research examines the framing of the Rohingya crisis in Indonesia and Malaysia through A Critical Discourse Analysis (CDA) of two online newspaper stories, one from every country. The study uses appraisal theory to examine the attitudinal resources (emotion, judgement, and appreciation) employed in the articles in order to better understand how they may change public perceptions of the Rohingya. The analysis shows significant differences in how the crisis is portrayed by the two media outlets. The Indonesian article takes a positive and humanitarian stance, emphasizing Indonesia's commitment to global refugee protection and expressing concern for the well-being of Rohingya refugees. In contrast, the Malaysian article represents a shift towards a restrictive and nationalistic approach, highlighting concerns about national interests and depicting the Rohingya as a potential threat. Although the articles acknowledge the shared challenges faced by refugees, they also expose the complexity of regional responses to the Rohingya crisis and the divergent perspectives adopted by Indonesia and Malaysia. This study contributes to the understanding of how media discourse shape’s public opinion and influences ideological perspectives on international events.